Mercury biomagnification in a coastal Louisiana food web following the 2010 Deepwater Horizon oil spill - Lamb, Katelyn J.; Midway, Stephen R.; Brasso, Rebecka L.; López-Duarte, Paola C.; Kimball, Matthew E.; Polito, Michael J. (Frontiers in Environmental Science, 2022)
The estuarine environments surrounding coastal Louisiana create favorable conditions for microbially mediated mercury (Hg) methylation and subsequent bioaccumulation by biota. In 2010, the Deepwater Horizon (DWH) oil spill released large amounts of oil which, despite having low Hg concentrations, had the potential to influence methylmercury (MeHg) bioavailability in the coastal zone. To explore this possibility, we assessed Hg concentrations and trophodynamics in the coastal Louisiana food web prior to and immediately following the DWH oil spill and compared these metrics with an adjacent coastal ecosystem in the northern Gulf of Mexico. We found no differences in MeHg concentrations between oysters collected in years prior to the spill (1986–2007) and those collected during or in the months immediately after the spill (May to December 2010). When comparing tissue MeHg concentrations and carbon and nitrogen stable isotope values across 13 species of bivalves, shrimp, crabs, fishes, and birds we found evidence of significant biomagnification within the coastal Louisiana food web driven by species’ trophic position and their use of differing basal carbon sources. In addition, Hg trophodynamics also differed between two adjacent coastal ecosystems, post-spill coastal Louisiana (2010) and pre-spill coastal Alabama (2008–2009). While there was a higher trophic magnification factor in coastal Louisiana relative to coastal Alabama, food web baseline MeHg concentrations were higher in coastal Alabama. The high degree of biomagnification in coastal Louisiana, and significant regional variation, underscores the need to monitor Hg trophodynamics over space and time to better evaluate the short and long-term ecological consequences of events like the DWH oil spill.